Exploring research themes in the Journal of Librarianship and Information Science: Insights from topic modelings - Aslan, Alper; Özyurt, Özcan (Journal of librarianship and information science, 2025)
This study aims to explore research interests and trends in the journal by analyzing the entire publication history of the Journal of Library and Information Science (JoLIS) between 1969 and 2023 using Latent Dirichlet Allocation (LDA). A comprehensive topic modeling analysis was conducted on 1437 articles for which titles, abstracts and keywords were available. The research focuses on identifying key thematic shifts in the journal’s publications. The findings highlight that topics such as Information Literacy & Research and Librarian Roles & Skills are growing in importance, while traditional topics such as Cataloging & Classification are declining. The results reveal shifts in the focus of the LIS field, providing critical insights to guide future research. In particular, Information Literacy & Research emerges as a highly accelerating topic, reflecting the need for digital competencies in response to evolving information environments. Meanwhile, declining interest in Cataloging & Classification is in line with the automation of traditional library functions, shifting training priorities toward digital literacy and data management skills. By mapping the evolution of research priorities, this study serves as a valuable resource for LIS researchers and practitioners, helping them to align their work with future developments in the field.